Reflections of an American harpsichordist unpublished memoirs, essays, and lectures of Ralph Kirkpatrick - Kirkpatrick, Ralph 1911-1984 (University of Rochester Press, 2017)
Presents previously unpublished memoirs (1933-77), lectures, and essays by the eminent harpsichordist and scholar Ralph Kirkpatrick
Title from publisher's bibliographic system (viewed on 31 Aug 2018)
Part one. Memoirs, 1933-77 -- Part two. Reflections: On performing ; On recording ; On chamber music ; On harpsichords and their transport -- Part three. Essays: Elliott Carter's Double concerto (ca. 1973) ; On editing Bach's Goldberg variations: for Arthur Mendel (March 31, 1973) ; RK and music at JE [Jonathan Edwards College] (1983) ; The equipment and education of a musician (1971) ; Bach and Mozart for violin and harpsichord (ca. 1944) ; The early piano (broadcast on BBC Radio 3, Music weekly, September 23, 1973) -- Part four. Lectures (Yale University. 1969-71): Bach and keyboard instruments ; In search of Scarlatti's harpsichord ; Style in performance ; The performer's pilgrimage to the sources ; Private virtue and public vice in the performance of "Early music"
Keywords: Kirkpatrick, Ralph; Kirkpatrick, Ralph -- 1911-1984; Geschichte 1911-1984; Harpsichordists / Biography; Harpsichord music / History and criticism; Cembalist; Musikanschauung; USA; Aufsatzsammlung; Autobiografie; Biografie